2007
DOI: 10.1093/ndt/gfm023
|View full text |Cite
|
Sign up to set email alerts
|

New strategies in haemodiafiltration (HDF): prospective comparative analysis between on-line mixed HDF and mid-dilution HDF

Abstract: Mixed HDF was the most efficient technique in the highest range of safe operating conditions. In mid-dilution HDF, high pressures generated inside the dialyser compromised membrane permeability and limited the total infusion rate, resulting in an overall reduction in solute removal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 20 publications
0
21
0
Order By: Relevance
“…Two kinds of MIXED are currently proposed [7]. The first on the market was mid-dilution ol-HDF (MID) [8,9,10].…”
Section: Discussionmentioning
confidence: 99%
“…Two kinds of MIXED are currently proposed [7]. The first on the market was mid-dilution ol-HDF (MID) [8,9,10].…”
Section: Discussionmentioning
confidence: 99%
“…Mixed-dilution HDF is a relatively new modality where blood dilution is split between pre-and postfiltering and which was developed to achieve the best possible rheological and hydraulic conditions within the dialyzer and to optimize the fluid exchange rate and convective solute removal. However, a significant advantage of mixed-dilution over postdilution HDF in regard of P i removal still needs to be demonstrated [12] . Mixed dilution may be of special advantage in patients with high predialysis hematocrit and an increased risk of filter clotting with postdilution HDF due to hemoconcentration.…”
Section: Hemodiafiltrationmentioning
confidence: 99%
“…Sir, The report by Feliciani et al [1] on the comparison of online mixed haemodialfiltration (HDF) and mid-dilution HDF caused several concerns as to the validity of their results. Their decision, which was based on a misinterpretation of our own, earlier published work [2], not attempting to optimize anti-coagulation for mid-dilution HDF, may have resulted in insufficient heparin dosing and, subsequently, in very high pressures and reduced clearances, due to increasingly clotting of fibers.…”
Section: New Strategies In Haemodialfiltration (Hdf)--prospective Commentioning
confidence: 99%
“…According to our findings and experience, mid-dilution HDF with the Nephros MD220 filter is a safe and highly effective therapy mode, provided that adequate operating conditions have been chosen. Reply Sir, In a comparative study of two online haemodiafiltration techniques, published in NDT [1], we reported that, in middilution HDF, impressive high hydraulic pressures were recorded in the first section of the blood dialyser compartment, where post-dilution takes place. Scepticism on the validity of these findings, recently expressed by Krieter and Canaud in NDT [2], lies on the feeling that insufficient anti-coagulation caused partial fibre clotting and compromised the efficiency of our experimental sessions.…”
Section: New Strategies In Haemodialfiltration (Hdf)--prospective Commentioning
confidence: 99%